Increasing Nurse Retention Based On Internal Service Quality Approach In Batu Bara Hospital - Glorio Ias Natanael; Chrismis Novalinda Ginting; Santy Deasy Siregar (International Journal of Health and Pharmaceutical (IJHP), 2022)
One of the problems for human resource management is the desire to leave (turnover intentions) which can lead to the nurse's decision to leave her job. One way for nurses to stay in the hospital is to increase employee retention. The purpose of this study was to develop recommendations to increase employee retention based on the Internal service quality approach at Batu Bara Hospital. This research is descriptive research with a quantitative approach. This research was conducted at the Batu Bara Hospital from September 2020 to March 2022. The research population used was nurses who were actively working at the Batu Bara Hospital, totaling 105 people with a total sample of 105 respondents. Linear regression tests and multiple linear regression tests were used to determine the effect between the dependent variable and the independent variable. The results showed that the cooperation variable and role conflict variable had no effect on increasing nurse retention, and the variables of suitability to work, suitability to technology, self-control ability, supervisory system, and role ambiguity had an effect on increasing nurse retention at Batu Bara Hospital. In this study together the independent variables have an influence on the dependent variable with a large effect of 95.9%. Suggestions for the Batu Bara Hospital should further strengthen the relationship between nurses by holding regular meetings, providing knowledge to nurses about the organizational components of Batu Bara Hospital through guidance from managers/supervisors and regular training to nurses, improving the quality of existing job designs that can This is done by completing the equipment and technology needed by nurses and reviewing the existing reward system, where the reward system must implement a justice system based on the workload, education, work experience and achievements of nurses.